Equal before the (expressive power of) law? - Luise Görges; Tom Lane; Daniele Nosenzo; Silvia Sonderegger (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
Building on findings showing that laws exert a causal effect on social norms, this paper investigates whether this "expressive power of law" differs by gender or race. We develop a model to show that such differences are theoretically plausible. We then use an incentivized vignette experiment to test whether these differences are empirically relevant. Results from an online sample of around 4000 subjects confirm that laws causally influence social norms. However, we find little evidence of a differential effect across gender or race, suggesting that gender and race biases in the legal system are driven by other mechanisms than differences in the expressive power of law.
Keywords: C91; C92; D9; K1; K42; 330; Social Norms; Law; Expressive Function of Law; Gender Gap; Racial Bias